The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Biofouling effect of different landfill leachates on high-density polyethylene pipe material - Rui Zhao; Mengheng Luo; Min Li; Hongwei Yang; Zhuo Zeng (Process Safety and Environmental Protection, 2024)

Contrasting fracturing and cementation timings during shale gas accumulation and preservation: An example from the Wufeng-Longmaxi shales in the Fuling shale gas field, Sichuan Basin, China - Tao Luo; Xiaowen Guo; Zhiliang He; Jian-xin Zhao; Ze Tao; Tian Dong; Rui Yang; Junlin Chen (Marine and Petroleum Geology, 2024)

Effective purification of Fe/V as spherical phosphosiderite and porous vanadium oxyhydroxide from waste vanadium-bearing slag - Zhu Suiyi; Su Ting; Lan Xin; Htet Oo Kaung; Zheng Minglin; Wang Tianzhu; Luo Wenjing; Zhou Rui; Yang Weilu; Chen Yu (Journal of Water Process Engineering, 2024)

Study on desulfurization and modification of high-sulfur petroleum coke via reduced iron powder catalytic roasting - Pen Luo; Zhengjie Chen; Xiuhua Chen; Wenhui Ma; Xiaowei Gan; Rui Xie (Journal of Environmental Chemical Engineering, 2024)

Highly selective separation of 99TcO4−/ReO4− with rapid liquid-liquid two-phase disengagement by amine-diamide ligands - Long Li; Xuanhao Huang; Xiaoyang Hu; Xingyue Liu; Rui Li; Hang Zhou; Fengfeng Li; Fangxiang Luo; Qingjiang Pan; Songdong Ding (Journal of Environmental Chemical Engineering, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Effect of yeast (Saccharomyces cerevisiae) fermentation on conformational changes in pig liver proteins and their ability to bind to characteristic aldehydes - Jin Luo; Li Liang; Jingcheng Zhang; Yongzhao Bi; Rui Yang; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2024)

Metabolomic analysis of umami taste variation in Pyropia haitanensis throughout the harvest cycle - Zihan Yuan; Haibin Pan; Juanjuan Chen; Yuting Zhang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2024)

Fucoidan from Sargassum hemiphyllum (Turner) C. Agardh inhibits human hepatoma cell (HepG2) through cell cycle arrest and apoptotic induction - Yanzhe Chen; Xiaofei Liu; Jianping Chen; Baozhen Luo; Feifei Zhu; Rui Li; Zhuo Wang; Kit-Leong Cheong; Saiyi Zhong (Food Bioscience, 2024)

Development of radio frequency drying protocols for preserving the color and fragrance of lotus bee pollen - Xuan Luo; Dingting Zhou; Gaoji Yang; Juanjuan Xu; Yong Luo; Rui Li; Shaojin Wang (Food Control, 2024)

Utilization of waste biomass to produce SiO2/SiC nanowires with efficient electromagnetic wave absorption performance - Rui Xie; Zhengjie Chen; Wenhui Ma; Yonghang Zhang; Xiaowei Gan; Xiaowei Chen; Pen Luo (Chemical Engineering Journal, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Watershed-oriented and multifactor-integrated identification and hazard evaluation of debris-flow-prone watersheds in Danba, China - Xiaojun Luo; Mingyue Hou; Jiayin Fan; Rui Li; Jiawen Bao; Chenhao Li; Hang Li; Jie Deng (Landslides, 2024)

Adventitious shoot organogenesis from immature leaves of sugarcane (Saccharum spp. hybrid) cultivar Yuetang 03-373 improving shoot proliferation and industrial scale-up of plants - Shuangyan Chen; Yinglin Lu; Qingwen Luo; Jiana Tan; Jinyan Guan; Jianpiao Luo; Yuchan Xu; Mengyi Chen; Rui Zhao; Jaime A. Teixeira da Silva; Yifei Zhang; Guohua Ma (Journal of Crop Science and Biotechnology, 2024)

Spatiotemporal Characteristics of Atmospheric Brown Carbon Emission from Combustion Sources in China - Shuyu Ouyang; Ke Jiang; Rui Xiong; Yatai Men; Zhihan Luo; Ran Xing; Guofeng Shen (Chinese Geographical Science, 2024)

Multi-dimensional simulation of the segmented thermoelectric generator applied in the heat pipe reactor based on COMSOL - Aoguang Wu; Kefan Zhang; Weixiang Wang; Rui Pan; Shuai Wang; Xiao Luo; Hongli Chen (Annals of Nuclear Energy, 2024)

Yam (Rhizoma Dioscoreae) polysaccharide affects growth performance, immunity, and intestinal microbial community in Bulatmai barbel (LucioBarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Gaochao Wang; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

Oreonectes yuedongensis (Cypriniformes, Nemacheilidae), a new freshwater fish species from the Lianhua Mountains in eastern Guangdong, China - Chang‐Ting Lan; Tao Luo; Xin‐Rui Zhao; Jing Yu; Ning Xiao; Jiang Zhou (Journal of Fish Biology, 2024)
In this work, we describe a new species of the genus Oreonectes , Oreonectes yuedongensis sp. nov., collected from the Lianhua Mountains in eastern Guangdong, China. Phylogenetic trees constructed based on the mitochondrial cytochrome b ( Cyt b ) gene showed that this new species represents an independent evolutionary lineage, with uncorrected genetic distances (Kimura 2‐parameter model) from congeners ranging from 5.1% to 8.3%. In addition, nuclear DNA analysis indicated O. yuedongensis as an independent lineage separate from its closely related species. Morphologically, the new species can be distinguished from other six species in the genus Oreonectes by a combination of serial characters. The description of this new species suggests that it is necessary to reassess the biodiversity of Oreonectes platycephalus as a complex, especially in the middle reaches of the Pearl River near the border between Guangdong and Guangxi. Morphological and genetic evidence supports O. yenlingi as a synonym of O. platycephalus .

Changes in phycospheric and environmental microbes in Neoporphyra haitanensis during the cultivation cycle - Qiqin Liu; Rui Yang; Yepengyu Gu; Denghui Gu; Juanjuan Chen; Qijun Luo; Haimin Chen (Aquaculture, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Review on microwave immobilization of soil heavy metals: Processes and mechanisms - Huiyin Huang; Juan Luo; Rui Ma; Dengcai Zhang; Shichang Sun; Chaoyong Du (Journal of Environmental Management, 2024)

Urban synergistic carbon emissions reduction research: A perspective on spatial complexity and link prediction - Bin Zhang; Jian Yin; Rui Ding; Shihui Chen; Xinyuan Luo; Danqi Wei (Journal of Environmental Management, 2024)

Dual-mode SERS/colorimetric sensing of nitrite in meat products based on multifunctional au NPs@COF composite - Rui Tan; Mei Zeng; Qiuwen Huang; Na Zhou; Mengjiang Deng; Yuanyuan Li; Xiaojun Luo (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Mg and Fe co-loaded biochar prepared by microwave-synergized K2FeO4 of marine biomass for efficient CO2 capture: Performance assessment and mechanism exploration - Juan Luo; Kai Sun; Shichang Sun; Rui Ma; Chongwei Cui; Han Cui (Chemical Engineering Journal, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Mn vacancy engineering design of Fe/Mn based cathodes for breaking the spell between “sodium limiting” in air-stabilization and “sodium promoting” on kinetics - Rui Huang; Shaohua Luo; Qi Sun; Xin Yan; Haoran Zhang; Lixiong Qian; Xin Liu; Xingzhong Cao; Peng Zhang; Shengxue Yan (Chemical Engineering Journal, 2024)

Construction of ROS-balancing-engineered heterojunction photoswitch for achieving programmed inflammatory management and tissue regeneration - Bin Luo; Jing He; Jiahui Lei; Rui Wen; Xiaoqin Hu; Fang Lan; Yao Wu (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Prolonged exposure to NaAsO2 induces thyroid dysfunction and inflammatory injury in Sprague‒Dawley rats, involvement of NLRP3 inflammasome‒mediated pyroptosis - Lili Fan; Qian Song; Ying Jin; Rui He; Heng Diao; Peng Luo; Dapeng Wang (Archives of Toxicology, 2024)

A comprehensive conceptual framework for signaling in-lake CO2 through dissolved organic matter - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Shengjun Wu; Zhikang Wang; Jing Zhang; Xiaodan Wang; Yongmei Ma (Water Research, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Enhanced nitrogen and phosphorus removal by iron-manganese mediated autotrophic denitrification in electrochemical system and the underlying mechanisms - Rui Gan; Ke Zhang; Hongbing Luo; Jia Chen (Process Safety and Environmental Protection, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Reducing moisture content can promote the removal of pathogenic bacteria and viruses from sheep manure compost on the Qinghai-Tibet Plateau - Rongrong Li; Rui Cai; Xi Luo; Yuru Liu; Lu Zhang; Wenbo Yu; Zhe Yang (Journal of Environmental Chemical Engineering, 2024)

Regulating the structure and gelling properties of maize starch by non-thermal effect of low intensity radio frequency wave - Dingting Zhou; Gaoji Yang; Xuan Luo; Juanjuan Xu; Hosahalli S. Ramaswamy; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The role of male hormones in bacterial infections: enhancing Staphylococcus aureus virulence through testosterone-induced Agr activation - Zhaoxia Luo; Huimin Xi; Wei Huang; Mei-fang Liu; Lei Yuan; Qiang Chen; Yanghua Xiao; Qing Zhu; Rui Zhao; Yi-yun Sheng (Archives of Microbiology, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Transient response of semi-elliptical hill with an elliptical tunnel under blast and seismic loading - Hao Luo; Ming Tao; Zheng Yang; Rui Zhao; Chengqing Wu (Soil Dynamics and Earthquake Engineering, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Decoding polyphenol metabolism in patients with Crohn’s disease: Insights from diet, gut microbiota, and metabolites - Liyuan Xiang; Shuyu Zhuo; Wanrong Luo; Chunyang Tian; Shu Xu; Xiaozhi Li; Yijun Zhu; Rui Feng; Minhu Chen (Food Research International, 2024)

Amphibole fractionation as a key driver for oxidation of magmas in convergent margins - Chen-Hao Luo; Rui Wang; Oliver Nebel; Qi-Wei Li (Earth and Planetary Science Letters, 2024)

Micromechanical anisotropic damage approach for understanding localized behavior of brittle materials under tension - Qiaojuan Yu; Shigui Du; Qizhi Zhu; Yunxing Lu; Zhanyou Luo; Rui Yong (Computers and Geotechnics, 2024)

Cu-substituted Na0.75Ni0.17Cu0.08Mn0.75O2 cathode with suppressing P2-O2 phase transition and air-stable for high-performance sodium-ion batteries - Guodong Hao; Shao-hua Luo; Pengyu Li; Ge Wang; Wei Zhao; Rui Huang; Haoran Zang; Jiachen Wang; Lixiong Qian (Chemical Engineering Journal, 2024)

Liquidizing crystal MIL-100(Fe) to coating silica powder for purifying wastewater - Shiyong Wei; Aijia Cao; Siyuan Huang; Yao Shen; Ting Lei; Songmei Luo; Mingjun Cai; Wenjun Xiang; Anying Chen; Rui Wang (Chemical Engineering Journal, 2024)

Effects of anaerobic oxidation of methane (AOM) driven by iron and manganese oxides on methane emissions in constructed wetlands and underlying mechanisms - Ke Zhang; Rui Gan; Yangxingyue Li; Wei Chen; Dandan Ma; Jia Chen; Hongbing Luo (Chemical Engineering Journal, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Castor Bean Meal Fertilizer Improves Peanut Yield and Quality by Regulating the Soil Physicochemical Environment and Soil Enzyme Activities - Mingjing Li; Rui Luo; Mingda Yin; Zhiyan Wang; Zhimin Su; Xiaohui Gu; Xuemei Hu; Chi Zhang; Fenglan Huang (Journal of Soil Science and Plant Nutrition, 2024)
Purpose Fertilization is important for improving crop yield and soil quality. Elucidation of the effects of castor bean meal (CBM) fertilizer on peanut yield and quality and soil fertility can lead to additional fertilization options for peanut and provide a theoretical reference for achieving a high-quality, high-yielding peanut. Methods During 2022–2023, a two-year long-term field experiment was conducted in Tongliao city, Inner Mongolia, China. No fertilizer (CK) was used as the control, and the effects of different treatments, i.e., CBM fertilizer (B1: 2520 kg ha -1 , B2: 5040 kg ha -1 , and B3: 10,080 kg ha -1 ), chemical fertilizer alone (F1: 175 kg ha -1 , F2: 350 kg ha -1 , and F3: 700 kg ha -1 ), and cow manure alone (N1: 3724 kg ha -1 , N2: 7448 kg ha -1 , and N3: 14,896 kg ha -1 ) on peanut yield and quality and soil fertility were investigated. Results The results showed that CBM fertilizer application improved soil ecology. Compared with other fertilization treatments, the soil pH of B3 treatment decreased by 8.5%, but significantly increased the contents of organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), total potassium (TK), alkali-hydrolyzed nitrogen (AN), basic phosphorus (AP) and rapidly available potassium (AK) in the soil, which increased by 86.4%, 64.6%, 70.5%, 11.3%, 75.8%, 150.1%, and 116.2%, respectively, compared with CK. Meanwhile, B1, B2, N1 and N2 treatments also led to the elevation of the above indexes. In addition, the activities of urease (URE), sucrase (SUC), phosphatase (PPL), catalase (CAT), amylase (AMY) and protease (PRO) in the B3 treatment were significantly greater than those in the other fertilization treatments, with increases of 256.4%, 248.4%, 68.2%, 96.8%, 267.3%, and 155.7%, respectively, compared with CK. The B3 treatment also significantly increased the rootlet length(PRL), number of branches(BN), plant height(PLH) and lateral branch length(LBL) of the peanut plants. Compared with the other treatments, the B3 treatment had a greater peanut yields, reaching 8059.5 kg ha -1 and 9935.7 kg ha -1 in 2022 and 2023, respectively. Compared with the other treatments, the B1 treatment significantly increased the contents of protein (Pro), fat (FAT), unsaturated fatty acid (UFA) and vitamin E (VE), which increased by 23.3%, 6.1%, 1.0%, 29.1%, respectively, compared with CK, but the total sugar (TS) content was reduced by 9.1%. Correlation analysis further confirmed that peanut yield and quality were significantly correlated with soil nutrients and enzyme activities. Conclusions This study showed that the application of CBM fertilizer has certain positive effects. For example, the B3 treatment has certain potential for increasing peanut yield, and the B1 treatment can be used for peanut quality improvement. Therefore, CBM fertilizer is recommended as a new type of organic fertilizer for improving the peanut quality and yield.

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Adaptation mechanisms of soil microbial community to stoichiometric imbalances caused by forest conversion - Xianzhen Luo; Lingling Zhang; Zhi Li; Rui Zhang; Johannes J. Le Roux; Jason K. Reynolds; Hanxia Yu; Minghao Chen; Yahong Zheng; Enqing Hou; Dazhi Wen (Applied Soil Ecology, 2024)

Heat transfer characteristics analysis of heat pipe based on COMSOL - Rui Pan; Kefan Zhang; Weixiang Wang; Aoguang Wu; Wenpei Feng; Xiao Luo; Hongli Chen (Annals of Nuclear Energy, 2024)

Effect of tunnel ventilation on surrounding rock temperature field and heat regulating circle during construction phase - Ming-Rui Luo; Yu-Chun Tao; Zuo-Bing Yuan; Liang-Liang Tao; Chuan He; Yan-Ping Yuan; Xiao- Yu Tian; Yan-Hua Zeng (Tunnelling and Underground Space Technology, 2024)

Long-term mulched drip irrigation enhances the stability of soil aggregates by increasing organic carbon stock and reducing salinity - Mingdong Tan; Wenhao Li; Rui Zong; Xuanzhi Li; Yue Han; Pengcheng Luo; Yam Prasad Dhital; Haixia Lin; Haiqiang Li; Zhenhua Wang (Soil and Tillage Research, 2024)

Highly oxidized guaiane 12(8),15(6)-dilactones with neuroprotective activities from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Si-Qing Lou; Hong-Yu Chen; Di Luo; Lu Guo; Ning-Yu Chen; Rui Wu; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

June insolation gradient and ice sheet forcing on Qaidam precipitation during the middle Piacenzian warm period - Zeng Luo; Hansheng Wang; Richard V. Heermance; Junsheng Nie; Jing Yang; Xiaoli Yu; Zhao Wang; Rui Zhang; Qingda Su (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Optimization of ecological network function and structure by coupling spatial operators and biomimetic intelligent algorithm - Zhaomin Tong; Ziyi Zhang; Yanchi Lu; Yaolin Liu; Rui An; Xuan Luo; Sui Liu; Bin Zhang (Journal of Cleaner Production, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Covalent organic framework with bioinspired N,S-anchored single atom sites for photocatalytic CO2 reduction reaction - Zi-Xian Pan; Shuai Yang; Xi Chen; Jing-Xian Luo; Rui-Zhi Zhang; Peng Yang; Qing Xu; Jie-Yu Yue (Chemical Engineering Journal, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Anthropogenic effects on soils in the eastern Tibetan Plateau revealed by geochemical elemental characteristics - Yuanlong Luo; Shengli Yang; Chen Wen; Xuechao Xu; Xue Xiao; Jiantao Zhou; Xiuyun Yang; Rui Li; Jingzhao Zhang; Xiaomin Fang (Environmental Research, 2024)

The role of hormones in the regulation of lactogenic immunity in porcine and bovine species - Kexin Hua; Dan Liu; Qianshuai Xu; Yuna Peng; Yu Sun; Rongrong He; Rui Luo; Hui Jin (Domestic Animal Endocrinology, 2024)

Untargeted LC–MS metabolomics reveals the metabolic responses in the Eriocheir sinensis gills exposed to salinity and alkalinity stress - Shihui Wang; Yingying Song; Liang Luo; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Boosting peroxymonosulfate activation over partial Zn-substituted Co3O4 for florfenicol degradation: Insights into catalytic performance, degradation mechanism and routes - Xinyang Wang; Xinyu Luo; Rui Li; Yu Chang; Jianbiao Peng; Weilai Wang; Haijin Liu; Guangxuan Yan; Pengkun Wei; Zhiguo Cao (Chemical Engineering Journal, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Orthorhombic K3V3(PO4)4: A low-temperature cathode material for potassium-ion batteries - Rui-Jie Luo; Chong-Yu Du; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Zi-Ting Zhou; Ze-Yu Zhu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Cytokines-activated nuclear IKKα-FAT10 pathway induces breast cancer tamoxifen-resistance - Xueyan Chen; Weilin Wu; Ji-Hak Jeong; Matjaz Rokavec; Rui Wei; Shaolong Feng; Werner Schroth; Hiltrud Brauch; Shangwei Zhong; Jun-Li Luo (Science China Life Sciences, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Diclofenac sodium effectively inhibits the biofilm formation of Staphylococcus epidermidis - Huimin Xi; Zhaoxia Luo; Mei-fang Liu; Qiang Chen; Qing Zhu; Lei yuan; Yi-yun Sheng; Rui Zhao (Archives of Microbiology, 2024)

Bidirectional biotic interchange between Taiwan Island and Mainland China via land bridges—A case study of Obeidia Walker (Geometridae, Lepidoptera) - Rui Cheng; Nan Jiang; A’rong Luo; Michael Orr; Qingsong Zhou; Xiaoyu Shi; Hongxiang Han; Chaodong Zhu (Zoologica Scripta, 2024)
Biotic exchanges between Taiwan and Mainland China have shaped the biodiversity and ecosystems of both regions. Exchanges from Mainland China to Taiwan have received more attention, mainly studied in terrestrial vertebrates, while the reverse direction and invertebrates have largely been overlooked. Here, we explore the dispersal events between these two regions based on the moths of three species groups of Obeidia , including Taiwan taxa and its relatives from mainland. We conducted mixed methods and analysis, including reconstructing a phylogenetic tree, estimating associated divergence times and inferring ancestral areas and source regions, to explore the phylogeographical structure and genetic pattern of three groups based on eight genes. Our results revealed a structure of three clades and every clade included at least one Taiwanese taxa and its closest relatives of mainland of China, and also served Taiwan as an important source region of two mainland taxa. Our study revealed various origin pattern and dispersal models on the basis of three species groups of Obeidia . Bi‐directional biotic exchange via a land bridge were found: four Taiwanese taxa originated from mainland, and two of them migrated back to mainland. Both eastern Himalayas and south China are important origin areas for Taiwan biota, and the dominant source region may need multiple insect cases to confirm. Our study also provided evidences for disjunct distribution from the perspective of insecta molecular phylogeny.

Multi-objective optimization driven by preponderant individuals and symmetric sampling for operational parameter design in aluminum electrolysis process - Lizhong Yao; Jia Chen; Ling Wang; Rui Li; Haijun Luo; Jun Yi (Swarm and Evolutionary Computation, 2024)

Cadmium pollution exacerbated by drought: Insights from the nanoscale interaction at the clay mineral surface - Guantong Tian; Qi Luo; Rui Xing; Jianguo Zhang; Xiong Li (Science of The Total Environment, 2024)

Identification of extracellular polymeric substances layer barrier in chloroquine phosphate-disturbed anammox consortia and mechanism dissection on cytotoxic behavior by computational chemistry - Rui Hu; Xue Chen; Mengting Xia; Bin Chen; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2024)

Thermoacoustic refrigeration with compressible liquid as working fluid - Rui Yang; Yupeng Yang; Jingyuan Xu; Zhanghua Wu; Ercang Luo (International Journal of Refrigeration, 2024)

Emplacement mechanism of ponded light plains on the Moon: Insight from topography roughness - Wei Cao; Zhiyong Xiao; Fanglu Luo; Yizhen Ma; Hanxing Ouyang; Rui Xu (Icarus, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Adaptive strategies of high and low nucleic acid prokaryotes in response to declining resource availability and selective grazing by protozoa - Chen Hu; Liuqian Yu; Xiaowei Chen; Jihua Liu; Yao Zhang; John Batt; Xilin Xiao; Qiang Shi; Rui Zhang; Tingwei Luo; Nianzhi Jiao; Dapeng Xu (Science China Earth Sciences, 2024)
Prokaryotes play a fundamental role in global ocean biogeochemical cycles. However, how the abundance and metabolic activity of ecologically distinct subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells), and their regulating factors, change in response to changing marine environmental conditions remains poorly understood. Here, we delved into the time-evolving dynamic responses of the HNA and LNA prokaryotic subgroups to declining resource availability and selective grazing by protozoa by conducting a 73-day incubation experiment in a large-volume (117,000 L) macrocosm that facilitates community-level exploration. We found that the metabolic activity of the HNA subgroup was higher than that of the LNA subgroup when the macrocosm was resource replete but that the HNA subgroup declined more rapidly than the LNA subgroup as the resources became increasingly scarce, leading to a steadily increasing contribution of LNA cells to prokaryotic activity. Meanwhile, as resources in the macrocosm became limited, protozoan grazing preference shifted from the HNA to the LNA subgroup and the contributions of the LNA subgroup to the carbon flow within the macrocosm increased. The findings highlight the resilience of LNA cells in resource-limited environments, illuminate the critical role of selective grazing by protozoa in balancing distinct prokaryotic subgroups under changing resource conditions, and demonstrate the complex and adaptive interactions between protozoa and prokaryotes across diverse environmental contexts.

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Clinical Characteristics and Pathogen Spectrum of Male Genital Fungal Infections in Nanchang Area, South China - Yun Jin; Yangmin Gao; Yunpeng Luo; XiaoHua Tao; Qing Jiang; Xinyi Fan; Rui Xu; Hua Qian; Xiaoguang Li; Zhijun Zhou (Mycopathologia, 2024)
The cutaneous fungal infections in male genitalia are relatively rare, and often present with various atypical clinical symptoms. It was mainly reported in a small number of case reports, while data with large number of patients were rarely reported. In this study, we reported 79 male patients with cutaneous fungal infections on scrotum or penis. The fungal infections were confirmed by microscopic examination directly and fungus culture. Clinical characteristics and predisposing factors were also collected. Of these 79 patients, 72 has lesions on scrotum, 5 on penis and 2 on both scrotum and penis. Trichophyton (T.) rubrum is the most common pathogen, found in 50 (67.6%) patients, which presented diverse clinical manifestation such as majorly erythematous, dry diffused scaly lesions without a clear border, slightly powdery and scutular scalings. Candida (C.) albicans is the secondly common pathogen, found in 21 (28.4%) patients, which also presented diverse lesions such as erythematous with dry whitish scaly lesions and erythematous erosion. The predisposing factors mainly included concomitant fungal infections on sites other than genitalia, especially inguinal region (tinea cruris), application of corticosteroid and high moisture. In conclusion, cutaneous fungal infections in male genitalia could be caused by different fungi, showed atypical or mild clinical appearances in most cases and might be a fungus reservoir, emphasizing the necessity to timely perform the fungi examinations and corresponding therapy.

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

A highly stable electrochemical sensor with antifouling and antibacterial capabilities for mercury ion detection in seawater - Weichen Meng; Xiaochun Han; Rui Han; Xinchao Zhang; Xianghua Zeng; Jizhou Duan; Xiliang Luo (Analytica Chimica Acta, 2024)

Investigation of 200 anthropogenic activities in a representative alpine peatland in the Altay Mountains, northwestern China - Nana Luo; Rui Yu; Bolong Wen; Xiaoyu Li; Qilin Zhang; Xiujun Li (Environmental Science and Pollution Research, 2024)
Peatlands records can be used to reconstruct and understand the history of environmental evolution, as well as a more accurate reflection of human activities. The black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) are ideal natural archives of anthropogenic activities. To identify the information of anthropogenic activities recorded by peatlands in the middle and high latitudes of the alpine mountains in the arid and semi-arid regions of China. this study analyzed the concentrations of BC, δ 13 C ratios of BC, PAHs, and molecular diagnostic ratios of PHAs (including Benzo(a) anthracene (BaA), Chrysene (Chr), fluoranthene (Flt), anthracene (Ant), phenanthrene (Phe), Benzo(a) pyrene (BaP), and pyrene (Pyr) in a 30-cm peat profile from the Altay Mountain, northwestern China. Our results revealed concentrations of BC from 11.71 to 67.5 mg·g −1 , and PAHs from 168.09 to 263.53 ng·g −1 . The δ 13 C BC value ranged from − 31.37 to − 26.27‰, with an average of − 29.54‰, indicating that the BC mainly comes from biomass combustion. The ratios of BaA/(BaA + Chr), Flt/(Flt + Pyr), and Ant/(Ant + Phe) exceeded 0.35, 0.5, and 0.1, respectively, revealing that the PAHs pollutants mainly originated from the combustion of biomass and fossil fuel burning. Furthermore, based on these findings and our knowledge of social development in Altay, industrial transport and tourism have influenced the emission, transport, and deposition of BC and PAH in peatlands in the Altay mountains since the 1980s. After 1980, pollutant concentrations decreased with the implementation of environmental policies. The results not only reveal the influence of anthropogenic activities on the sedimentary characteristics of peatlands in the Altay Mountains, but also provide an important theoretical basis for the conservation of fragile mountain peatlands.

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

SERS detection of triazole pesticide residues on vegetables and fruits using Au decahedral nanoparticles - Zhinan Chen; Rui Tan; Mei Zeng; Xue Yuan; Kaiyi Zhuang; Changsheng Feng; Yi He; Xiaojun Luo (Food Chemistry, 2024)

Enhanced peroxymonosulfate activation for degradation of iodinated contrast media by microwave-induced bimetallic carbon-based catalysts: Insight into the synergistic mechanism between microwaves and bimetallic sites - Zixia He; Zhen Tian; Juan Luo; Shichang Sun; Guopeng Zhu; Rui Ma (Chemical Engineering Journal, 2024)

Mechanisms of soil organic carbon stabilization and its response to conversion of primary natural broadleaf forests to secondary forests and plantation forests - Xianzhen Luo; Rui Zhang; Lingling Zhang; Adam Frew; Hanxia Yu; Enqing Hou; Dazhi Wen (CATENA, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Pseudomonas aeruginosa regulator PvrA binds simultaneously to multiple pseudo-palindromic sites for efficient transcription activation - Yibo Zhu; Bingnan Luo; Xingyu Mou; Yingjie Song; Yonghong Zhou; Yongbo Luo; Bo Sun; Youfu Luo; Hong Tang; Zhaoming Su; Rui Bao (Science China Life Sciences, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Rapid immobilization of arsenic in contaminated soils by microwave irradiation combined with magnetic biochar: Microwave-induced electron transfer for oxidation and immobilization of arsenic (III) - Dengcai Zhang; Junhao Lin; Juan Luo; Shichang Sun; Xi Zhang; Rui Ma; Juan Peng; Fei Ji; Shuaifei Zheng; Zhen Tian; Ning Ma (Science of The Total Environment, 2024)

Mineral exploration model for Lhasa Area, eastern Gangdese metallogenic belt: Based on knowledge-driven compositional data analysis and catchment basin division - Bingli Liu; Wenbao Zheng; Lu Wang; Cheng Li; Yunhui Kong; Rui Tang; Dejiang Luo; Miao Xie (Journal of Geochemical Exploration, 2024)

Synergistic removal of sulphur-containing malodourous gases via peroxydisulfate activation in three-dimensional electrode system - Rui Luo; Shugen Liu; Chen Li; Xiaofeng Huang; Ping Ning; Senlin Tian (Journal of Environmental Chemical Engineering, 2024)

Effect of berry-derived phenolic products on blood lipid profiles: A systematic review and meta-analysis - Chunxiao Ji; Rui Wang; Dongliang Wang; Yongle Luo; Zaiming Huang; Jianying Liu; Anwei Cheng (Food Bioscience, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Water-assisted catalytic transfer hydrogenation of guaiacol to cyclohexanol over Ru/NiAl2O4 - Yuying Zhao; Jiahui Zhan; Rui Hu; Gang Luo; Jiajun Fan; James H. Clark; Shicheng Zhang (Chemical Engineering Journal, 2024)

Impacts of an upper tropospheric cold low on the extreme precipitation in Henan Province, China in July 2021 - Liangliang Li; Wenshou Tian; Jian Li; Jinlong Huang; Rui Wang; Jiali Luo (Atmospheric Research, 2024)

Alpha-Asarone Ameliorates Neurological Dysfunction of Subarachnoid Hemorrhagic Rats in Both Acute and Recovery Phases via Regulating the CaMKII-Dependent Pathways - Xiaofeng Gao; Rui Li; Lijun Luo; Can Liao; Huiyuan Yang; Shengjun Mao (Translational Stroke Research, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

An improved analytical model for rainfall infiltration in embankment slope constructed with red-bed solid waste - Jianqing Jiang; Shilin Luo; Jin Chang; Rui Zhang (Transportation Geotechnics, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Energy-efficient trehalose-based polyester nanofiltration membranes for zero-discharge textile wastewater treatment - Xiongwei Luo; Lei Jiang; Rui Zhao; Yue Wang; Xin Xiao; Sabrine Ghazouani; Lihua Yu; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Journal of Hazardous Materials, 2024)

Submicroscopic iron-rich grains throughout impact glasses in Chang'E-5 regolith - Pan Yan; Zhiyong Xiao; Yanxue Wu; Yunhua Wu; Qing Pan; Fanglu Luo; Rui Xu (Icarus, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Study and verification on an improved comprehensive prediction model of landslide displacement - Tianlong Wang; Rui Luo; Tianxing Ma; Hao Chen; Keying Zhang; Xu Wang; Zhaowei Chu; Hongyue Sun (Bulletin of Engineering Geology and the Environment, 2024)

The Effect of Artificial Substrate and Carbon Source Addition on Bacterial Diversity and Community Composition in Water in a Pond Polyculture System - Kun Guo; Mumin Shi; Xiaoli Huang; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Guoliang Ruan; Zhigang Zhao (Fishes, 2024)
The use of artificial substrates and biofloc technology can favor fish culture and improve water quality. The aim of this study was to evaluate whether artificial substrates and carbon source additions modify the microbial activity of water bodies. The diversity and structure of microflora in the water after adding artificial substrates and carbon sources to the ponds were analyzed using high-throughput sequencing based on the V3-V4 region of 16S rRNA genes. The results showed that there was no difference in the richness and diversity of intestinal microflora between the control and experimental groups. Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) showed that artificial substrate and carbon source addition changed the structure of the microflora. The results of a linear discriminant analysis (LDA) effect size (LefSe) indicated 11 biomarkers in the EGˍst group. Spearman correlation heatmap analysis showed that environmental factors affected the bacterial communities, and the results of a redundancy analysis indicated that chemical oxygen demand was a critical factor in controlling the bacterial communities in the water. These results provide an understanding of the effect of artificial substrate and carbon source addition on bacterial diversity and community composition in water.

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Soy protein isolate amyloid fibril-coated ZrO2 nanoparticles anchored in the polyurethane sponge for rapid and effective fluoride adsorption in the wide pH range - Wenjing Lu; Chunhui Zhang; Zhiwei Lin; Peidong Su; Zhaowei Qin; Xuezhi Li; Rui Wang; Yunchang Liu; Peiyao Luo; Kepeng Qiu (Journal of Environmental Chemical Engineering, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

A Novel Kunitz-Type Serine Protease Inhibitor (HcKuSPI) is Involved in Antibacterial Defense in Innate Immunity and Participates in Shell Formation of Hyriopsis cumingii - Can Jin; Kang Cheng; Rui Jiang; Yihang Zhang; Wen Luo (Marine Biotechnology, 2024)

Quercetin improved hepatic circadian rhythm dysfunction in middle-aged mice fed with vitamin D-deficient diet - Rui Li; Guiping Wang; Ruitong Liu; Lan Luo; Ying Zhang; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2024)

Parallelization and optimization for a pin-by-pin whole core thermal–hydraulic analysis code - Xiao Luo; Kefan Zhang; Junjia Zhang; Rui Pan; Aoguang Wu; Shuai Wang; Hongli Chen (Annals of Nuclear Energy, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

The synthesis and secretion of key substances in the flavonoid metabolic pathway responding to different nitrogen sources during early growth stages in Robinia pseudoacacia - Yuanli Li; Yongrui Shen; Rui Shi; Ziyi Yang; Yifu Chen; Wen Luo; Gehong Wei; Minxia Chou (Plant and Soil, 2024)

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)